INTERFERON BETA 1B FOR THE IMMUNOMODULATORY TREATMENT OF MULTIOCULAR SCLEROSIS IN PEDIATRIC NEUROLOGIC PRACTICES - O.V. Bykova; L.M. Kuzenkova; L.M. Vysotskaya; O.I. Maslova; A.N. Boiko (Union of pediatricians of Russia, 2006)
Medications for the immunomodulatory therapy of the multiocular sclerosis are widely spread and have been applied in adult neurologic practices for a long time, although the data about their use among the patients under 18 is scarce and not classified. We present the history of foreign and russian experience in application of the medication for the immunomodulatory therapy of the multiocular sclerosis - interferon beta 1b - among children and teenagers along with the brief analysis of the acquired data about effectiveness and safety of this type of treatment in pediatrics in the published research.Key words: multiocular sclerosis, immunomodulatory therapy, children, teenagers.